Symmetry in Quantum Theory of Gravity - Fields, Chris; Marciano, Antonino (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This edited collection explores current approaches to understanding space, time, and gravity within a quantum-theoretical framework. In most such approaches, the three-dimensional space of ordinary perception and action is physically fundamental, but is rather emergent from underlying structures or dynamics that can, in general, be described in terms of information flows. Processes such as measurement and computation are, therefore, fundamental to the notion of physical space.